Kupas Tuntas Model Media Pembelajaran Dan Bermain Pada Siswa TK ABA Podosugih Pekalongan - Fadli, Failasuf (THUFULA, 2018)
MODEL OF LEARNING AND PLAY MEDIA IN STUDENTS OF ABA PODOSUGIH PEKALONGAN KINDERGARTEN EDUCATION. Kindergarten Education is a formal institution for children to receive knowledge and technology. However, the problem is the difficulty of how to deliver educational materials, because at the age of kindergarten children is the age to play. So it needs attention in providing educational content material or aspects that are the objectives of learning. The purpose of the article that will be discussed is to describe any model that is a medium of learning in kindergarten education, in addition it is also expected to be able to thoroughly examine how the appropriate play model for early childhood. This study uses qualitative methods with primary sources of teachers and students in TK ABA podosugih Pekalongan. This research process through the stages of data reduction, data presentation and conclusion drawing. The final result of this study states that the kindergarten phase is a phase where fantasy power is very strong and always wants to play so that it requires a variety of learning media so that children are able to easily absorb the content of learning content in a fun way. In addition, in this study also explained the results of various kinds of media games for early childhood. So that it is hoped that later it will be able to open up the horizons of learning and playing media suitable for kindergarten students.